An Evaluation of Guidance Services in Senior Secondary Schools in the Central Region of Ghana - Sackey, Mary; Anterkyi Bentil,, Josephine; Asiedu, Alice (International Journal of Scientific Research and Management (IJSRM), 2020)
This study was conducted to find out what Guidance Service are being offered in the Senior Secondary Schools in the Central Region, their impact on students, the challenges and constrain that hinder their effective implementation. In trying to accomplish this study, related literature was reviewed. Descriptive survey was the design. Questionnaire was the main research instrument.  Three sets of questionnaires were designed for students, teachers and coordinators, pilot- tested and administered to collect data. Sample sizes of 262 respondents were involved in the study. It comprised 235 SSS 2 students and 3 students, 21 tutors and 6 guidance coordinators. The sample was selected using purposive sampling and simple random sampling techniques analysis, Percentages was used. The findings of the study indicate that pupil’s appraisal service, orientation service, counselling service, placement service, information service, Referral service and consultation service are being offered in the senior secondary schools. It came out that the services are appreciated by the students, and it was beneficial to students. Challenges and constraints faced include lack of office accommodation for effective guidance services, lack of funds to organized programmes and provision of in – service training for the coordinators. Recommendations include adherence to recommended teaching schedules for guidance coordinators and provision of office for the use of coordinators and for individual counselling